2019
DOI: 10.1590/s0102-865020190070000010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prognostic value of platelet-based prognostic models in patients with malignant hepatic tumors after TACE therapy

Abstract: Intellectual, scientific, conception and design of the study; acquisition, analysis and interpretation of data; technical procedures; statistical analysis; manuscript preparation, final approval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…), and lipid metabolism (including apolipoprotein A, total cholesterol, etc.) [15][16][17][18][19][20][21]. However, few of them have achieved worldwide acknowledgment.…”
Section: Introductionmentioning
confidence: 99%
“…), and lipid metabolism (including apolipoprotein A, total cholesterol, etc.) [15][16][17][18][19][20][21]. However, few of them have achieved worldwide acknowledgment.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by Du et al (32) analyzed the prognostic value of PLT-based prognostic scores in patients with advanced malignant hepatic tumors who had received transarterial chemoembolization (TACe) therapy and reported that APgA is an independent risk factor for the overall survival rate. however, the present study determined the performance value of various scoring systems on the prognostic of patients with malignant hepatic tumors who received various types of therapy, including TACe and hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…however, the present study determined the performance value of various scoring systems on the prognostic of patients with malignant hepatic tumors who received various types of therapy, including TACe and hepatectomy. In addition, only a small number of cases were included in previous studies and these studies only focused on the overall survival rate of patients (25,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation